La configuración de la tríada formativa en los territorios de la formación en Documentología. Relaciones entre sí y con el contexto de aplicación - Garay Brogg, José Luis (Archivos de criminología, seguridad privada y criminalística, 2023)
Throw a case study it’s proposed to describe the ways in which the training is expressed in the context of education of Documentology, particularly in the manners that involves to the training triad in the context of education, as well as the bound between this and the context of application. In this way, two territories have been descripted. The first one, the lesson-classroom, presents a relation between the trainer and the trainee asymmetric and an object approached from the theory. The second one, the forensic-classroom, the asymmetries are been overcame, and the object is approached through the practice.